Extending sexual scripting theory through critical discursive psychology: An analytical approach to explore the performance of sexual identities. - Healy-Cullen S; Morison T (SAGE Publications, 2024)
Sexual scripting theory, a widely used tool in sexuality research, was originally developed by Gagnon and Simon to illuminate the social nature of sexual practices and identity construction. Later, they sought to develop the theory further to align with a social constructionist perspective. However, vestiges of individualism and cognitivism haunt sexual scripting theory largely due to the use of the symbolic interactionist concept of performance. To address this, we draw on the performance–performativity approach in critical discursive psychology that develops the notion of performance from a discursive perspective and offers a way of extending sexual scripting theory that offers a truly social explication of sexual identity construction. We provide a practical illustration of this extended theorising, drawing on data from a project about young people’s online engagement with pornography. We demonstrate how developing the notion of sexual scripts as discursive resources that enable the performance of sexual identities allows us to illuminate the social and situated nature of identity construction. This framework enhances understanding of the process of sexual identity construction and provides a valuable tool for studying how broader sexual scripts that are sociohistorically specific provide a scaffolding for the ways an individual can construct sexual identities. Overall, this paper offers a valuable contribution to discursive scholarship in psychology by presenting a nuanced analytical framework that coheres with a constructionist, performative view of identity.
Keywords: sexuality; sexual scripting theory; critical discursive psychology; sexual identity; performance; performativity